Research Data Management in German Academia from a Multiple Logic Perspective - Eva Katharina Donner; Christian M. Huber (M@n@gement)
The requirements for research data management (RDM) have increased. Due to academia’s neoliberalization, however, researchers already face a high workload within a hypercompetitive environment. The demand to integrate RDM as an additional task into academics’ day-to-day actions seems to be quixotic. To deepen our understanding of early career researchers’ (ECRs) daily work arbitrage, we need to know more about their behavior, actions, and decisions in relation to RDM. Drawing on a multiple institutional logics perspective at the micro-level, we conducted 40 semistructured interviews at German higher education institutions (HEIs) to investigate how ECRs respond to institutional logics in the context of RDM. Our findings revealed three profiles – the conformist, the waverer, and the resister – that make use of different response strategies to the state, market, professional, and community logic. We contribute to institutional logic research at the micro-level and, in addition, broaden prior research on HEIs and RDM by taking neoliberal academia into account.